The Role of Big Data and Blockchain in Enabling Transparent and Sustainable Business Processes - Amroni, Amroni; Darmawan, Afif Aditya; Pangilinan, Greian April (ADI Journal on Recent Innovation, 2025)
The integration of Big Data and Blockchain technologies is increasingly vital for businesses aiming to foster transparent and sustainable processes in response to global demands for socially and environmentally responsible practices. However, research on how these technologies work together is still limited. This study, using the Business Oriented Management Research Cycle (BOMRC), investigates how Big Data and Blockchain can synergistically promote transparent and sustainable business practices. The research includes a literature review, case study analysis, and application of findings to practical business scenarios. The findings reveal that Blockchain enhances transparency and traceability through a decentralized, secure system, while Big Data provides real time data processing to optimize operational efficiency and reduce environmental impact. By leveraging the synergy between these technologies, businesses can improve sustainability and maximize performance. Despite these advantages, high implementation costs and technological challenges remain significant barriers. This study contributes to understanding how Big Data and Blockchain can work together to promote sustainability, providing insights for overcoming barriers to their adoption. Future studies should explore sector specific applications to further advance these technologies.